MODEL PROJECT BASED LEARNING TERHADAP KEMANDIRIAN MATEMATIS SISWA PADA MATERI BANGUN RUANG - Hidayat, Amam Taufiq (JP3M (Jurnal Penelitian Pendidikan dan Pengajaran Matematika), 2023)
Independence of students' mathematical learning are classified as not maximally explored by students in learning with the main focus on the teacher. So we need a learning model that involves student-centered activities. This study aims to see the effect of the Project Based Learning (PjBL) model on students' mathematical learning independence. The research uses quantitative methods with a quasi-experimental research type and a posttest only group design. The population is all students of class VII SMP Negeri 1 Nisam. With the purposive sampling technique, it was obtained that class VIIA students were the experimental class and VIIB class were the control class. The data collection technique used was the provision of a mathematical learning independence questionnaire. Hypothesis testing was carried out by analyzing the results of the mathematical learning independence questionnaire using the t-test with SPSS 25 with a significance level of 0.05. Based on data analysis obtained sig. the result of learning independence data testing is 0.000. Based on criteria for testing the hypothesis can be concluded that there is an influence of the PjBL model on students' mathematical learning independence in geometric material at SMP Negeri 1 Nisam.